An improved accurate monotonicity-preserving scheme for the Euler equations. (25th November 2016) - He, Zhiwei; Zhang, Yousheng; Gao, Fujie; Li, Xinliang; Tian, Baolin
Highlights: Two potential causes accounting for the weak robustness of the MP scheme are revealed. An improved version of the MP scheme is proposed. The improved scheme achieves a good compromise between resolution and robustness. Abstract: The accurate monotonicity-preserving (MP) scheme of Suresh and Huynh (1997) [5] is a high-order and high-resolution method for hyperbolic conservation laws. However, the robustness of the MP scheme is not very high. In this paper, a detailed analysis on this scheme is performed, and two potential causes which may account for the weak robustness are revealed. Furthermore, in order to enhance the robustness of the MP scheme, an improved version of the MP scheme is presented, in which a strict continuous total-variation-diminishing (TVD) numerical flux is used at a disturbed discontinuity so that oscillations cannot grow indefinitely without violating the TVD condition. Without destroying the very high resolution property, numerical tests show that the improved scheme shares a strong robustness in simulating extreme numerical tests.